The caldron of consciousness : motivation, affect and self-organization, an anthology - Ellis, Ralph D.; Newton, Natika (Advances in Consciousness Research, 2000)
From a neuropsychological perspective, awareness of emotions is a complex function involving several components (perceptual decoding and conceptualization, memory and attention, and psychophysiological responses). Pathological conditions of the nervous system as well as certain experimental procedures in healthy persons may induce dissociations of these components. It is suggested that perceptual awareness of an emotional stimulus requires a correct stimulus identification as well as input monitoring. Awareness of experiential qualities is a more global function involving integration of interoceptive information, formation of emotional schemas or concepts, and recall of episodic memory of past emotions. Perceptual awareness of internal or external stimulus events can be defined and measured by means of psychophysical methods. Experiental qualities, however, are difficult to assess in a reductionist/physicalist framework.